The Impact of the Digital Consumer's Emotional Intelligence in Relation to the Moral Values Promoted in E-Business - Bucur-Teodorescu, Ioana (Sustainable Management, Wertschöpfung und Effizienz, 2021)
XXI, 247 p. 46 illus., 41 illus. in color.